Do Remittances Boost Productivity? Asymmetric Evidence from Leading Asian Recipient Countries - Naseem, N. A. M.; Wanwan, L.; Nabila, H.; Azman-Saini, W. N. W.; Masron, T. A. (International Journal of Economics and Financial Issues, 2025)
This study attempts to examine the asymmetric effect of remittances on total factor productivity (TFP) growth in India, China, and the Philippines over 1982–2023 using a nonlinear ARDL (NARDL) benchmark specification that decomposes remittances into positive and negative shocks. The long-run nonlinear estimates show that TFP responses to remittances are state-dependent rather than uniform. Remittance adverse shocks have no significant effect in any country, suggesting that downturns are cushioned by countercyclical remitting, coping mechanisms, and diversified financing. Remittance positive shocks, however, are decisive: in India and China they boost TFP by easing liquidity constraints and supporting human and physical capital formation, while in the Philippines they reduce TFP through Dutch-disease effects, as inflows appreciate the exchange rate, shift resources to non-tradables, and weaken productivity gains. Thus, while India and China should channel remittance surges into productive investment to enhance TFP, the Philippines needs policies that curb Dutch-disease pressures and redirect inflows toward tradables, skills, and technology.